Academics on Professional Helpers’ Education: How Do They Perceive the Work-Related Challenges? - Emese Beáta Berei; Klára Kovács (Education Sciences)
There is research on professional helper education and jobs working in a society with children and youth or supporting vulnerable people, but for academics, working in higher education, and preparing students for these work fields, it is not very common. This research focuses on academics from five European countries who prepare teachers, medical, healthcare, and clergy professionals. The aim is to design a map of pressures and challenges in their work. We hypothesized that academics in professional helper higher education (PHHE) perceive work-related challenges differently. Using explanatory research methodology, we considered higher education responsibilities: the working time and demands of academics. A total of 315 responses were used in our quantitative analyses from Romania, Slovakia, Hungary, Serbia, and Ukraine. The research questions were as follows: Are there differences between academics’ responsibilities and different PHHE scientific fields or work profiles? How do academics cope with work tasks and work time? How is a long hour-working academic’s profile? Statistical analyses using SPSS included cross-tabulation analysis, ANOVA and correlation tests, and factor analysis. We delimited two scientific fields and four academic working profiles: 1. academics in teacher education; 2. academics in medical/healthcare education; 3. leaders; 4. organizers; 5. classic lecturers; and 6. researchers. We designed five work demand patterns: controls and supports, global pressures, performance pressures, multi-role challenges, and lecturer roles. Drawing the map of pressures, we concluded that there are significant differences between those in teacher education in perceiving global (research, grant, and publish) responsibilities and performance pressures. At the same time, classic lecturers have significantly higher scores on perceiving performance challenges, and we deduced a positive and significant relation between multi-role challenges and overworking time. The design of the long hour-working profile of academics in PHHE is significantly associated with the medical and health scientific field. Men and academics from E.U. countries have significantly higher working time scores than females and workers outside E.U. Leaders have the highest working mean-time score comparing all the working fields and profiles. Our results for higher education teachers, researchers, policymakers, and institutional leaders can be useful in identifying work-related difficulties and maintaining a balanced distribution of work in the academic fields.